2022
DOI: 10.1021/acs.iecr.1c04456
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Ni–Y/CeO2 Catalyst for Nonthermal Plasma Catalytic CO2 Methanation

Abstract: Nonthermal plasma (NTP)-assisted CO2 methanation can activate and convert stable CO2 molecules under ambient conditions as compared to conventional thermal catalysis (normal operation temperature up to 450 °C), which is a good technique to reduce CO2 emissions and simultaneously utilize the renewable energies like solar and wind. It is critical to develop a robust catalyst with good catalytic performance in order to make NTP catalytic CO2 methanation more competitive. Herein, we present a simple yet efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…NTP-catalytic CO 2 methanation over the catalysts under investigation was performed in a dielectric barrier discharge (DBD) reactor in a laboratory-scale plasma rig at ambient temperature (viz. 25 °C) described previously . Before the experiment, ∼300 mg of as-synthesized catalyst was in situ pre-treated in a 20% H 2 /Ar atmosphere for 30 min under the plasma condition at an applied peak voltage and a frequency of 9 kV and 7.7 kHz, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…NTP-catalytic CO 2 methanation over the catalysts under investigation was performed in a dielectric barrier discharge (DBD) reactor in a laboratory-scale plasma rig at ambient temperature (viz. 25 °C) described previously . Before the experiment, ∼300 mg of as-synthesized catalyst was in situ pre-treated in a 20% H 2 /Ar atmosphere for 30 min under the plasma condition at an applied peak voltage and a frequency of 9 kV and 7.7 kHz, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…NTP activation has the unslective nature, thus rational design of catalysts is considered one of the important aspects in the development of selective NTP-catalysis, which has been proposed and proved by us and other colleagues previously. For example, previously we have partially showed the effect of the catalyst physiochemical properties (such as pore structure, support size, and surface acidity/basicity) and active site accessibility on the interactions between the active metal sites and the plasma-induced active species and thus the performance of NTP-catalytic CO 2 hydrogenation. , In addition to catalyst development, in situ methods such as diffuse reflectance infrared Fourier transform spectroscopy and X-ray absorption fine-structure were developed as well to enable the mechanistic understanding of the surface phenomena of relevant NTP-catalytic systems, which helps the rational design and development of tailored catalysts. ,, In detail, in NTP-catalytic CO 2 hydrogenation, in situ studies showed that plasma-induced vibrationally excited CO 2 molecules could readily interact with dissociated H 2 species adsorbed on metal surface via the Eley–Rideal (E–R) pathway, which can overcome the kinetic limitation in CO 2 conversion. , Accordingly, to promote such interfacial interactions in NTP-catalysis, rational tailoring of active metal species is key to advance NTP-catalytic systems.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, the conversion of the produced CaCO 3 is the indirect utilization of the CaO-captured CO 2 . To date, conversion of CO 2 /carbonate to value-added chemicals or fuels has become a hot research field. However, efficient, selective, and energy-saving conversion of CO 2 /carbonate into methane (CH 4 ) is still a challenge due to their stabilities …”
Section: Introductionmentioning
confidence: 99%